Ethnobotanical knowledge of Isaan Laos tribe in Khong Chai District, Kalasin Province, Thailand with particular focus on medicinal uses - PIMTIDA NIAMNGON; SURAPON SAENSOUK; PIYAPORN SAENSOUK; AUEMPORN JUNSONGDUANG (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Niamngon P, Saensouk S, Saensouk P, Junsongduang A. 2023. Ethnobotanical knowledge of Isaan Laos tribe in Khong Chai District, Kalasin Province, Thailand with particular focus on medicinal uses. Biodiversitas 24: 6793-6824. Isaan Laos ethnic group in Khong Chai District, Kalasin Province, Thailand hold a unique ethnobotanical knowledge on plant utilization, yet such knowledge and wisdom are facing gradual erosion due to modernization. Therefore, this study aimed to investigate comprehensively the ethnobotanical knowledge on the uses of plants among the Isaan Laos ethnic group residing in Khong Chai District. Data was gathered between July 2022 and July 2023 via vegetation survey, semi-structured interviews and focus group discussions with 23 villagers residing in village adjacent to the forested area to collect data on plant local names and its utilization. The data was then analyzed for Cultural Important Index (CI), Informant Agreement Ratio (IAR), and Fidelity Level (%FL). In total, Isaan Laos ethnic group in Khong Chai District utilize 291 plant species belonging to 229 genera and 88 families for various purposes. These plants are further categorized into 12 groups based on their traditional uses, including 168 species used for food and spices, 109 species for medicinal purposes, 74 species for ornamental purposes, 40 species for construction materials, 35 species for beliefs and rituals, 27 species for fuels, 20 poisonous species, 17 species for beverages, 5 species for dyeing, 4 species for cosmetics and perfumery, 3 species for industrial crops and 2 species for apparel. Oryza sativa is the most often utilized plant, with a CI value of 4.74, followed by Senna siamea (3.39) and Pandanus amaryllifolius (3.30). The body ache with the highest Index of IAR=0.94 is associated with Curcuma longa, which has the highest values of Fidelity Level (%FL). The most common use of Curcuma longa is to treat flatulence and expelling wind, as well as skin illness. Additionally, Curcuma longa has the highest CI value of 9.83. This study recorded ethnobotanical data in detail as fundamental knowledge for the conservation of plants to be utilized by future generations.